2012
DOI: 10.1161/circulationaha.112.092098
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Magnetic Resonance Imaging Evaluation of Endothelial Permeability in Murine Atherosclerosis Using an Albumin-Binding Contrast Agent

Abstract: Background-Endothelial dysfunction promotes atherosclerosis and precedes acute cardiovascular events. We investigated whether in vivo magnetic resonance imaging with the use of an albumin-binding contrast agent, gadofosveset, could detect endothelial damage associated with atherosclerosis in apolipoprotein E-deficient (ApoE Ϫ/Ϫ ) mice. Furthermore, we tested whether magnetic resonance imaging could noninvasively assess endothelial function by measuring the endothelial-dependent vasodilation in response to acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 55 publications
9
128
2
Order By: Relevance
“…MSA is not visible at the vascular tree, including the aorta, when injected intravenously in normal animals because of its large molecular size (17). However, the permeability around the endothelia that has been damaged by vascular inflammation at the atherosclerotic plaques is high enough for albumin to diffuse into the vessel wall (27). Further, we confirmed the persistence of 68 Ga-NOTA-MSA at the atherosclerotic aorta from 10 to 120 min after injection.…”
Section: Discussionsupporting
confidence: 61%
“…MSA is not visible at the vascular tree, including the aorta, when injected intravenously in normal animals because of its large molecular size (17). However, the permeability around the endothelia that has been damaged by vascular inflammation at the atherosclerotic plaques is high enough for albumin to diffuse into the vessel wall (27). Further, we confirmed the persistence of 68 Ga-NOTA-MSA at the atherosclerotic aorta from 10 to 120 min after injection.…”
Section: Discussionsupporting
confidence: 61%
“…Extravasation Assay-Vascular permeability was examined by visualizing the leakage of Evans blue dye into the vascular wall as described previously (32). WT and 12/15-LO Ϫ/Ϫ mice that were fed a chow diet or high fat diet were anesthetized by ketamine/xylazine, and Evans blue dye (0.1 ml of 1% Evans blue dye in phosphate-buffered saline) was injected into the inferior vena cava.…”
Section: Reagents-5(s)-hete 12(s)-hete 15(r)-hete 15(s)-hete Antimentioning
confidence: 99%
“…Lately, it was shown that contrast-enhanced MRI using iron oxide-and gadolinium-based contrast agents can visualize atherosclerotic lesions in young ApoE −/− mice in the brachiocephalic artery, a predilection site for atherosclerotic lesions. 26,27 A recent study from our group indicated that the change in cross-sectional vessel area during systole, a parameter related to vascular elasticity, is already impaired in the early stages of atherosclerosis. 28 The systolic cross-sectional change in vessel area, however, is not an independent parameter of vascular elasticity because it depends on cardiac output.…”
Section: Discussionmentioning
confidence: 99%